Pengaruh Kualitas Produk, Persepsi Harga, dan Lokasi terhadap Kepuasan Konsumen pada Restaurant Pandawa di Hotel Darmawan Park Sentul - Frecillia Ananda BB; Leonardo Indra Vitaharsa (Tamilis Synex: Multidimensional Collaboration, 2024)
This research aims to discuss and analyze product quality, price and location perceptions on consumer satisfaction at the Pandawa Restaurant at the Darmawan Park Sentul Hotel. The population in this study were all Darmawan Training and Consulting staff in all divisions. The research method used was purposive sampling. Data was collected through questionnaires from 150 customers at the Pandawa restaurant at the Darmawan Park Hotel. Data analysis was carried out using multiple linear regression analysis with the help of SPSS for Windows software. The results in this study show that product quality has a significant effect on customer satisfaction, price perception has a significant effect on customer satisfaction, and location has a significant effect on customer satisfaction.